In the republic of happiness : an entertainment in three parts - Crimp, Martin, 1956- (London : Faber And Faber, 2012)
A family Christmas is interrupted by the unexpected arrival of Uncle Bob. Who is he? Why has he come? Why does his wife stay out in the car? And what is the meaning of his long and outrageous message? All we can be sure of is that the world will never be the same again. In the Republic of Happiness is a provocative roll-call of contemporary obsessions.
-- 1 Destruction of the family -- 2 The five essentials freedoms of the individual -- 3 In the republic of happiness.
Keywords: Families -- Drama